2004
DOI: 10.1672/0277-5212(2004)024[0562:ieborn]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Invertebrate egg banks of restored, natural, and drained wetlands in the prairie pothole region of the United States

Abstract: Analogous to 'seed banks,' 'egg banks' are important for seasonal succession and maintenance of invertebrate species diversity throughout wet and dry cycles in the prairie pothole region. Further, recruitment of invertebrates from relic egg banks in the sediments and dispersal of eggs into wetlands is believed to be important for reestablishment of invertebrates in recently restored wetlands. Alhough tens-ofthousands of wetlands have been restored in the prairie pothole region of the United States, studies hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 20 publications
1
25
1
Order By: Relevance
“…Both richness and taxon-specific abundance of zooplankton hatching from the agriculturally modified CC sections was much lower compared to the reference sections, especially EM. These results corroborate trends found in a previous hatching study (Gleason et al, 2004), who found that the eggbanks of restored wetlands had significantly higher invertebrate taxon richness and abundance than drained wetlands. A study of aquatic invertebrates in temporary wetlands in the Camargue, France, concluded that species richness had a positive relationship with hydroperiod length, but a negative one with salinity (Waterkeyn et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Both richness and taxon-specific abundance of zooplankton hatching from the agriculturally modified CC sections was much lower compared to the reference sections, especially EM. These results corroborate trends found in a previous hatching study (Gleason et al, 2004), who found that the eggbanks of restored wetlands had significantly higher invertebrate taxon richness and abundance than drained wetlands. A study of aquatic invertebrates in temporary wetlands in the Camargue, France, concluded that species richness had a positive relationship with hydroperiod length, but a negative one with salinity (Waterkeyn et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Stressors may alter how invertebrate resting stages break dormancy, or block cues that trigger emergence, leaving propagules viable but still dormant (Angeler and García 2005). Furthermore, Gleason et al (2004) observed that many practices used in modern agriculture have a negative impact on the viability of invertebrate egg banks. Boulton and Lloyd (1992) showed that flood frequency and duration combined with water origin affected the composition of aquatic invertebrates that emerged from wetland sediments.…”
Section: Discussionmentioning
confidence: 99%
“…Gleason et al (2004) and Stanczak and Keiper (2004) showed that invertebrate resilience was similar between natural and restored wetlands mainly due to the existence of resting stages that remain viable over the dry period. However, the recovery of aquatic invertebrates via egg banks and/or other resistance structures has not been studied in rice fields.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations